Формування емоційного інтелекту майбутніх фахівців соціальної сфери у закладах вищої освіти - Кірсанов, Іван Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Дисертація на здобуття наукового ступеня доктора філософії зі спеціальності 011 «Освітні, педагогічні науки». – Національний технічний університет «Харківський політехнічний інститут», Міністерство освіти і науки України, Харків, 2026. У дисертації здійснено теоретичний аналіз проблеми та запропоновано нове вирішення наукового завдання, яке полягає у виявленні, теоретичному обґрунтуванні педагогічних умов та експериментальній перевірці їх впливу на сформованість емоційного інтелекту майбутніх фахівців соціальної сфери у закладах вищої освіти. Об’єкт дослідження – процес професійної підготовки майбутніх фахівців соціальної сфери у закладах вищої освіти. Предмет дослідження – педагогічні умови формування емоційного інтелекту майбутніх фахівців соціальної сфери у закладах вищої освіти. Метою дослідження є виявлення впливу науково обґрунтованих і експериментально перевірених педагогічних умов формування емоційного інтелекту майбутніх фахівців соціальної сфери у закладах вищої освіти на рівень сформованості означеної якості. Thesis for a PhD in Pedagogical Sciences in the specialty 011 “Educational, pedagogical sciences”. – National Technical University “Kharkiv Polytechnic Institute”, Ministry of Education and Science of Ukraine, Kharkiv, 2026. In the dissertation, a theoretical analysis of the problem was carried out and a new solution to the scientific task was proposed, which consists in identifying, theoretically substantiating pedagogical conditions and experimentally testing their influence on the formation of emotional intelligence of future social sphere specialists in higher education institutions. The object of the study is the process of professional training of future social sphere specialists in higher education institutions. The subject of the study is the pedagogical conditions for the formation of emotional intelligence of future social sphere specialists in higher education institutions. The purpose of the study is to identify the influence of scientifically substantiated and experimentally proven pedagogical conditions for the formation of emotional intelligence of future social sphere specialists in higher education institutions on the level of formation of their emotional intelligence.
The Formation of Emotional Intelligence of Future Specialists in the Social Sphere in Higher Education Institutions
Keywords: майбутній фахівець; емоційний інтелект; соціальна сфера; емоційна компетентність; фахова підготовка; формування; навчально- методичний інструментарій; future specialist of a social sphere; emotional intelligence; social sphere; emotional competence; professional training; formation; educational and methodological tools